A New 3D Autonomous Continuous System with Two Isolated Chaotic Attractors and Its Topological Horseshoes. (21st November 2017) - Zhou, Ping; Ke, Meihua
Abstract : Based on the 3D autonomous continuous Lü chaotic system, a new 3D autonomous continuous chaotic system is proposed in this paper, and there are coexisting chaotic attractors in the 3D autonomous continuous chaotic system. Moreover, there are no overlaps between the coexisting chaotic attractors; that is, there are two isolated chaotic attractors (in this paper, named "positive attractor" and "negative attractor, " resp.). The "positive attractor" and "negative attractor" depend on the distance between the initial points (initial conditions) and the unstable equilibrium points. Furthermore, by means of topological horseshoes theory and numerical computation, the topological horseshoes in this 3D autonomous continuous system is found, and the topological entropy is obtained. These results indicate that the chaotic attractor emerges in the new 3D autonomous continuous system.